2012
DOI: 10.1186/1475-2867-12-36
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lycopene on cell viability and cell cycle progression in human cancer cell lines

Abstract: BackgroundLycopene, a major carotenoid component of tomato, has a potential anticancer activity in many types of cancer. Epidemiological and clinical trials rarely provide evidence for mechanisms of the compound’s action, and studies on its effect on cancer of different cell origins are now being done. The aim of the present study was to determine the effect of lycopene on cell cycle and cell viability in eight human cancer cell lines.MethodsHuman cell lines were treated with lycopene (1–5 μM) for 48 and 96 h.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
74
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(87 citation statements)
references
References 38 publications
7
74
0
1
Order By: Relevance
“…A major trend in cancer research focuses on the activity of natural products and dietary factors reported to reduce cancer incidence (22)(23)(24)(25). However, in contrast to the low dietary levels associated with cancer prevention, the doses of such substances required to induce death of cancer cells may not be achievable in patients without producing toxic side-effects (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…A major trend in cancer research focuses on the activity of natural products and dietary factors reported to reduce cancer incidence (22)(23)(24)(25). However, in contrast to the low dietary levels associated with cancer prevention, the doses of such substances required to induce death of cancer cells may not be achievable in patients without producing toxic side-effects (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have showed that by eating tomato the breast (Zhang et al, 2009), head and neck cancers incidents were decrease (Freedman et al, 2008) and tomato may also be strongly protective against neurodegenerative diseases (Rao and Balachandran, 2002). Lycopene from the fruit and α-tomatine from the leaves of tomato showed anti-oxidant and anti-cancer activity to few cancer cell lines in-vitro and in-vivo (Shieh et al, 2011;Palozza et al, 2011;Chao et al, 2012;Kelkel et al, 2011;Lee et al, 2012;Teodoro et al, 2012;Tuzcu et al, 2012;Sharoni et al, 2012). In addition, previous studies have reported that tomato leaves synthesize glycoalkaloid dehydrotomatine and α-tomatine, which may have anticancer properties (Friedman, 1995;Friedman, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Lycopene is a major carotenoid found in tomato which has potent anticancer activity in many types of cancer. [6] The antioxidant properties of lycopene are thought to be primarily involved in its preventive effects in chronic diseases. It also has potent benefits in oral potentially malignant lesions like leukoplakia.…”
Section: Change In Mouth Opening Among Group Bmentioning
confidence: 99%